The use of adaptive intensity-modulated radiotherapy in the treatment of small-cell carcinoma lung refractory to chemotherapy in a patient with preexisting interstitial lung disease - Sarthak Tandon; Munish Gairola; Manoj Pal; Archana Aggarwal; Kanika Sharma; Ahmad Masroor Karimi; Avik Mandal; Rajiv Goyal; Ullas Batra; Inderjit Kaur (Lung India, 2018)
This is a case report of a 60-year-old diabetic, hypertensive male with a good performance status and a history of bilateral interstitial lung disease with a left upper lobe lung mass diagnosed to be a Stage IIB mixed small-cell/squamous cell carcinoma which was refractory to carboplatin- and etoposide-based chemotherapy. The patient was then taken up for adaptive intensity-modulated radiotherapy with tighter margin under image guidance with a mid-treatment replanning done at 25#. Acute toxicities were assessed weekly and showed no Grade 3 or more reactions. Pulmonary function test showed no detrimental changes during or after radiation. Response assessment at 12 and 20 weeks showed a partial response with decrease in metabolic activity on serial scans.